An electrochemical detector for biofilm formation - Espírito Santo, I. A. C. P. (1999)
On-line detectors of biofilm - platinum electrodes - were calibrated and validated in the laboratory under defined conditions, using a bacterium known as a good biofilm producer, Pseudomonas fluorescens. The electrochemical technique used was cyclic voltammetry.